Isolated facial palsy: a new lacunar syndrome. Issue 1 (January 1984) - Huang, C Y; Broe, G
Abstract : Three cases of sudden isolated upper motor neuron facial palsy and two with associated pseudobulbar palsy have been seen. All were without significant limb weakness. Computed tomography demonstrated small deep infarcts in the internal capsular/corona radiata regions. Pure upper motor neuron facial palsy may be another lacunar syndrome, due to a lesion in the internal capsule or corona radiata.